REAT: A Regional Economic Analysis Toolbox for R - Wieland, Thomas (REGION, 2019)
Methods of regional economic analysis are widely used in regional and urban economics as well as in economic geography. This paper introduces the REAT (Regional Economic Analysis Toolbox) package for the programming environment R, which provides a collection of mathematical regional analysis methods in a user-friendly way. The focus is on the identification of regional inequality, beta and sigma convergence, measurement of agglomerations, point-based measures of clustering and accessibility as well as regional growth. The theoretical basics of the applications are briefly introduced, while the usage of the most important functions is presented and explained using real data.